Resin composition, pellet, and molded article

By blending aromatic sulfonate salts with polycarbonate resin and titanium oxide, the resin composition achieves improved impact resistance and moisture resistance, addressing the inferior impact strength of molded products in existing technologies.

JP2025040776APending Publication Date: 2025-03-25MITSUBISHI ENG PLASTICS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023147791
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The impact strength of molded products obtained from polycarbonate resin compositions blended with titanium oxide is inferior, posing a challenge in achieving excellent impact resistance.

Method used

Incorporating a predetermined amount of aromatic sulfonate alkali metal salt and/or aromatic sulfonate alkaline earth metal salt into the resin composition containing polycarbonate resin and titanium oxide, specifically with 0.01 to 3.0 parts by mass of the salt per 100 parts by mass of polycarbonate resin, and ensuring the sulfate ion content is between 5,000 to 50,000 ppm.

Benefits of technology

The proposed solution enhances the impact resistance and moisture resistance of the molded products while suppressing the increase in viscosity, thereby improving the overall performance of the resin composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040776000001
    Figure 2025040776000001
  • Figure 2025040776000002
    Figure 2025040776000002
  • Figure 2025040776000003
    Figure 2025040776000003
Patent Text Reader

Abstract

To provide a resin composition containing a polycarbonate resin and titanium oxide which can provide a molded article excellent in impact resistance, a pellet, and a molded article.SOLUTION: A resin composition contains, with respect to 100 pts.mass of a polycarbonate resin (A), 5.0 to 20.0 pts.mass of titanium oxide particles (B), and 0.01 to 3.0 pts.mass of alkali metal salt of an aromatic sulfonic acid and / or alkali earth metal salt of an aromatic sulfonic acid (C), where a content of sulphate ions (SO42-) in the alkali metal salt of the aromatic sulfonic acid and / or the alkali earth metal salt of the aromatic sulfonic acid (C) is 5,000 to 50,000 mass ppm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a pellet, and a molded article, and in particular to a resin composition containing a polycarbonate resin as a main component. [Background technology]

[0002] 2. Description of the Related Art Titanium oxide has conventionally been blended into polycarbonate resin for the purpose of improving the shielding properties and coloring of resin molded products (Patent Document 1, Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2019 / 172243 [Patent Document 2] JP 2019-123809 A Summary of the Invention [Problem to be solved by the invention]

[0004] As described above, titanium oxide particles may be blended into a resin composition containing a polycarbonate resin. However, when titanium oxide is blended into a polycarbonate resin, the impact strength of a molded article obtained from the resin composition tends to be deteriorated. The present invention aims to solve the above problems, and to provide a resin composition containing a polycarbonate resin and titanium oxide, which is capable of providing a molded article having excellent impact resistance, a pellet, and a molded article. [Means for solving the problem]

[0005] In light of the above-mentioned problems, the present inventors have conducted research and have found that the above-mentioned problems can be solved by further blending a predetermined amount of an aromatic sulfonic acid alkali metal salt and / or an aromatic sulfonic acid alkaline earth metal salt to a resin composition containing a polycarbonate resin and titanium oxide. Specifically, the above problems were solved by the following means. <1> For 100 parts by mass of polycarbonate resin (A), 5.0 to 20.0 parts by mass of titanium oxide particles (B); and 0.01 to 3.0 parts by mass of an aromatic sulfonic acid alkali metal salt and / or an aromatic sulfonic acid alkaline earth metal salt (C), The sulfate ion (SO4 2- ) is 5,000 to 50,000 ppm by mass. <2> Furthermore, the aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) contains 1500 to 10000 mass ppm of phosphate ion (PO4 3- ), <1> The resin composition according to claim 1. <3> The aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) includes an alkali metal salt of diphenylsulfonic acid and / or an alkaline earth metal salt of diphenylsulfonic acid. <1> or <2> The resin composition according to claim 1. <4> The aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) includes potassium diphenylsulfone-3-sulfonate. <1> ~ <3> 10. The resin composition according to claim 9 . <5> For use as a light guide for automobile lighting or for use as a light guide for lighting. <1> ~ <4> 10. The resin composition according to claim 9 . <6> Furthermore, the aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) contains 1500 to 10000 mass ppm of phosphate ion (PO4 3- ), the aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) comprises potassium diphenylsulfone-3-sulfonate; The viscosity average molecular weight of the polycarbonate resin (A) is 10,000 to 35,000, and the polycarbonate resin (A) is used for a light guide for an automobile lamp or a light guide for illumination. <1> ~ <5> 10. The resin composition according to claim 9 . <7> <1> ~ <6> 2. A pellet of the resin composition according to claim 1. <8> <1> ~ <6> 2. A molded article formed from the resin composition according to claim 1. <9> <7> A molded article formed from the pellets according to claim 1. Effect of the Invention

[0006] According to the present invention, it is possible to provide a resin composition containing a polycarbonate resin and titanium oxide, which is capable of providing a molded article having excellent impact resistance, a pellet, and a molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.

[0008] The resin composition of the present embodiment contains 5.0 to 20.0 parts by mass of titanium oxide particles (B) and 0.01 to 3.0 parts by mass of an aromatic sulfonic acid alkali metal salt and / or an aromatic sulfonic acid alkaline earth metal salt (C) relative to 100 parts by mass of a polycarbonate resin (A). The amount of sulfate ions (SO4 2- ) is 5,000 to 50,000 ppm by mass. By using such a composition, a resin composition capable of providing a molded product having excellent impact resistance can be obtained. Also, a resin composition having excellent resistance to moist heat can be obtained. In this embodiment, it is believed that the aromatic sulfonate alkali metal salt and / or aromatic sulfonate alkaline earth metal salt (C) (hereinafter sometimes referred to as "sulfonate metal salt (C)") suppresses the aggregation of titanium oxide particles (B). Furthermore, titanium oxide particles (B) are usually surface-treated in the form of secondary particles, but when shear force is applied, they become primary particles, and some of the reactive hydroxyl groups of the titanium oxide particles (B) become exposed on the surface. In this embodiment, it is presumed that the sulfate ions or phosphate ions in the sulfonate metal salt (C) act on the reactive hydroxyl groups exposed on the surface of the titanium oxide particles (B), thereby minimizing damage to the polycarbonate resin (A). Furthermore, by using a metal sulfonate (C) containing a predetermined amount of sulfate ions, the increase in viscosity could be suppressed, especially during retention. The present invention will be described in detail below.

[0009] <Polycarbonate resin (A)> The resin composition of the present embodiment contains a polycarbonate resin (A). Specifically, the polycarbonate resin (A) is not particularly limited as long as it contains a -[OR-OC(=O)]- unit (wherein R is an organic group, preferably a hydrocarbon group, more preferably an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and further has a straight-chain structure or a branched structure) containing a carbonate bond in the molecular main chain. In this embodiment, the polycarbonate resin (A) is preferably an aromatic polycarbonate resin, more preferably a polycarbonate resin having a bisphenol skeleton, and more preferably at least one of bisphenol A type polycarbonate resin, bisphenol C type polycarbonate resin, and bisphenol AP type polycarbonate resin, and more preferably a bisphenol A type polycarbonate resin. By using such a polycarbonate resin, better heat resistance and toughness can be achieved. In the present embodiment, the polycarbonate resin having a bisphenol skeleton preferably contains, of all structural units, 90 mol % or more of structural units having a bisphenol skeleton (preferably structural units having a bisphenol A type skeleton), and more preferably contains, of all structural units, 95 mol % or more of structural units having a bisphenol skeleton.

[0010] The viscosity average molecular weight (Mv) of the polycarbonate resin (A) is preferably 10,000 or more, more preferably 12,000 or more, and even more preferably 15,000 or more. By making it equal to or more than the lower limit, the durability of the molded article obtained tends to be further improved. The upper limit of the viscosity average molecular weight (Mv) of the polycarbonate resin (A) is preferably 35,000 or less, more preferably 32,000 or less, and even more preferably 30,000 or less. By making it equal to or less than the upper limit, the molding processability of the molded article tends to be further improved. The viscosity average molecular weight (Mv) was calculated by using methylene chloride as a solvent and an Ubbelohde viscometer to determine the intrinsic viscosity [η] (unit: dL / g) at 25°C, and then using the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 ×Mv 0.83 , means a value calculated from When two or more types of polycarbonate resins are used, the viscosity average molecular weight is the mixture.

[0011] The method for producing the polycarbonate resin (A) is not particularly limited, and polycarbonate resins produced by the conventionally known phosgene method (interfacial polymerization method) or melting method (ester exchange method) can be used. When the melting method is used, a polycarbonate resin having an adjusted amount of OH groups at the terminal groups can be used.

[0012] The polycarbonate resin (A) used in this embodiment may be a recycled polycarbonate resin product (including recovered products, material recycled products, chemical recycled products, etc.), a rejected product, or a scrap from thermoplastic resin molding.

[0013] In addition to the above, details of the polycarbonate resin (A) can be referred to in paragraphs 0013 to 0041 of JP 2021-084942 A and in paragraphs 0030 to 0035 of JP 2021-119211 A, the contents of which are incorporated herein by reference.

[0014] The proportion of the polycarbonate resin (A) in the resin composition of this embodiment is preferably 83% by mass or more, more preferably 85% by mass or more, and even more preferably 87% by mass or more. By making it equal to or more than the lower limit, the impact resistance of the obtained molded article tends to be improved. In addition, the proportion of the polycarbonate resin (A) in the resin composition of this embodiment is preferably 95% by mass or less, more preferably 93% by mass or less. By making it equal to or less than the upper limit, the light blocking property of the obtained molded article tends to be improved. The resin composition of the present embodiment may contain only one type of polycarbonate resin (A), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0015] <Titanium oxide particles (B)> The resin composition of the present embodiment contains titanium oxide particles (B). By containing titanium oxide particles (B), light-blocking properties can be achieved in the obtained molded article. The titanium oxide particles (B) are usually particles having the highest titanium oxide content, and the proportion of titanium oxide in the titanium oxide particles (B) is 85.0% by mass or more, and preferably 90.0% by mass or more. An example of the titanium oxide particles (B) is one that contains 90.0 to 98.0 mass% TiO2 and Al2O3, preferably 90.0 to 98.0 mass% TiO2, Al2O3, and SiO2, and more preferably 90.0 to 98.0 mass% TiO2, 0.5 to 3.5 mass% Al2O3, and 0 to 6.0 mass% SiO2. Furthermore, the titanium oxide particles (B) may contain 0 to 0.1 mass% SO3, 0 to 0.15 mass% Na2O, and 0 to 0.01 mass% Cl in addition to the above components. Furthermore, the titanium oxide particles (B) may contain other components, the total of which is 100 mass%. Each component in the titanium particles (B) is measured by fluorescent X-rays and calculated in terms of oxide. Specifically, it is evaluated by semi-quantitative measurement. The total of the oxides is taken as 100% by mass, and the percentage of each oxide is expressed as a mass% value. For the measurement, a ZSX Primus manufactured by Rigaku Corporation can be used.

[0016] In this embodiment, the titanium oxide particles (B) may be either rutile type titanium oxide particles or anatase type titanium oxide particles. In addition, the titanium oxide particles (B) are preferably surface-treated with a surface treatment agent. By adopting such a constitution, the titanium oxide is more easily dispersed in the polycarbonate resin (A), and a molded article with a better appearance can be obtained. The surface treatment agent preferably contains the above-mentioned Al2O3 and / or SiO2. The surface treatment agent may be physically adsorbed or chemically bonded to the titanium oxide surface. The titanium oxide is usually titanium dioxide.

[0017] In this embodiment, the resin composition contains 5.0 to 20.0 parts by mass of titanium oxide particles (B) per 100 parts by mass of polycarbonate resin (A). By making it equal to or less than the upper limit, the effect of suppressing the deterioration of physical properties during retention tends to be improved. On the other hand, by making it equal to or more than the lower limit, the effect of improving light blocking properties tends to be improved. In this embodiment, the content of the titanium oxide particles (B) is preferably 6.0 parts by mass or more, more preferably 7.0 parts by mass or more, and even more preferably 9.0 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin (A). In this embodiment, the content of the titanium oxide particles (B) is preferably 19.0 parts by mass or less, more preferably 18.0 parts by mass or less, even more preferably 15.0 parts by mass or less, and even more preferably 12.0 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). The resin composition of the present embodiment may contain only one type of titanium oxide particles (B), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0018] <Alkaline metal aromatic sulfonate and / or alkaline earth metal aromatic sulfonate (C)> The resin composition of the present embodiment contains an aromatic sulfonic acid alkali metal salt and / or an aromatic sulfonic acid alkaline earth metal salt (sulfonic acid metal salt (C)). By containing the sulfonic acid metal salt (C), a resin composition having excellent impact resistance can be obtained. The metal sulfonate (C) is preferably an alkali metal salt. Examples of the alkali metal constituting the metal sulfonate (C) include lithium (Li), sodium (Na), potassium (K), rubidium (Rb), and cesium (Cs). Among these, sodium, potassium, and cesium are preferred, sodium and potassium are more preferred, and potassium is even more preferred. Examples of the alkaline earth metal constituting the metal sulfonate (C) include beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba) and radium (Ra), with magnesium and calcium being preferred.

[0019] The metal sulfonate (C) is preferably an alkali metal salt of diphenylsulfonic acid and / or an alkaline earth metal salt of diphenylsulfonic acid.

[0020] Preferred examples of the sulfonate metal salt (C) include dipotassium diphenylsulfone-3,3'-disulfonate, potassium diphenylsulfone-3-sulfonate, sodium benzenesulfonate, sodium (poly)styrenesulfonate, sodium paratoluenesulfonate, sodium (branched)dodecylbenzenesulfonate, sodium trichlorobenzenesulfonate, potassium benzenesulfonate, potassium styrenesulfonate, potassium (poly)styrenesulfonate, potassium paratoluenesulfonate, potassium (branched)dodecylbenzenesulfonate, potassium trichlorobenzenesulfonate, cesium benzenesulfonate, cesium (poly)styrenesulfonate, cesium paratoluenesulfonate, cesium (branched)dodecylbenzenesulfonate, cesium trichlorobenzenesulfonate, and the like, with potassium diphenylsulfone-3-sulfonate being more preferred.

[0021] Metal sulfonates (C) are sulfate ions (SO4 2- ) is 5,000 to 50,000 ppm by mass. By making it equal to or more than the lower limit, the effect of protecting the active surface of titanium oxide tends to be improved. Also, by making it equal to or less than the upper limit, decomposition of polycarbonate resin can be effectively suppressed. The sulfate ions are presumed to be derived from a synthesis catalyst or the like. The sulfate ion (SO4 2-The content of ) relative to the sulfonate metal salt (C) is preferably 8,000 ppm by mass or more, more preferably 10,000 ppm by mass or more, even more preferably 15,000 ppm by mass or more, still more preferably 20,000 ppm by mass or more, even more preferably 25,000 ppm by mass or more, and is preferably 45,000 ppm by mass or less, more preferably 40,000 ppm by mass or less, and even more preferably 38,000 ppm by mass or less.

[0022] Metal sulfonates (C) are phosphate ions (PO4 3- The phosphate ions are presumed to be derived from a synthesis catalyst or the like. The phosphate ion (PO4 3- The content of ) is preferably 1,500 mass ppm or more, more preferably 1,700 mass ppm or more, even more preferably 2,000 mass ppm or more, and even more preferably 2,300 mass ppm or more, relative to the sulfonic acid metal salt (C), and is preferably 10,000 mass ppm or less, more preferably 8,000 mass ppm or less, even more preferably 5,000 mass ppm or less, even more preferably 3,500 mass ppm or less, and even more preferably 3,000 mass ppm or less. By making it equal to or more than the lower limit, the effect of protecting the active surface of titanium oxide tends to be further improved. Also, by making it equal to or less than the upper limit, decomposition of the polycarbonate resin can be effectively suppressed.

[0023] The sulfate ion (SO4 2- ) and phosphate ion (PO4 3-) is preferably 10,000 ppm by mass or more, more preferably 15,000 ppm by mass or more, even more preferably 20,000 ppm by mass or more, still more preferably 25,000 ppm by mass or more, and even more preferably 30,000 ppm by mass or more, and is preferably 50,000 ppm by mass or less, more preferably 45,000 ppm by mass or less, and even more preferably 42,000 ppm by mass or less, relative to the sulfonate metal salt (C).

[0024] The metal sulfonate (C) may or may not contain a chloride ion. The chloride ions (Cl - The content of ) relative to the sulfonate metal salt (C) is preferably 5.0 ppm by mass or more, more preferably 10.0 ppm by mass or more, even more preferably 100.0 ppm by mass or more, still more preferably 300.0 ppm by mass or more, even more preferably 800.0 ppm by mass or more, and is preferably 1500.0 ppm by mass or less, more preferably 1300.0 ppm by mass or less, and even more preferably 1000.0 ppm by mass or less, and may be 500.0 ppm by mass or less, 400.0 ppm by mass or less, 250 ppm by mass or less, etc., depending on the application, etc.

[0025] The content of the sulfonic acid metal salt (C) in the resin composition of this embodiment is 0.01 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, and even more preferably 0.4 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin (A). The content of the sulfonic acid metal salt (C) is 3.0 parts by mass or less, preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, even more preferably 1.0 parts by mass or less, even more preferably 0.9 parts by mass or less, even more preferably 0.8 parts by mass or less, and even more preferably 0.6 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). By making it equal to or more than the lower limit, the effect of protecting the active surface of titanium oxide tends to be further improved. By making it equal to or less than the upper limit, the decomposition of the polycarbonate resin can be effectively suppressed.

[0026] The content of the sulfonate metal salt (C) in the resin composition of this embodiment is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and is preferably 1.0 mass% or less, more preferably 0.7 mass% or less, in the resin composition. The resin composition of the present embodiment may contain only one type of sulfonic acid metal salt (C), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0027] <Other ingredients> The resin composition of the present embodiment may contain other components as necessary, as long as the desired physical properties are not significantly impaired. Examples of the other components include various resin additives. Examples of resin additives include reactive compounds (e.g., epoxy compounds and / or oxetane compounds), stabilizers, release agents, ultraviolet absorbers, colorants (dyes, pigments), antistatic agents, flame retardants, flame retardant assistants, anti-dripping agents, anti-fogging agents, anti-blocking agents, flow improvers, plasticizers, dispersants, antibacterial agents, etc. The resin additives may be contained alone or in any combination and ratio of two or more.

[0028] <<Stabilizer>> The resin composition of the present embodiment may contain a stabilizer. The stabilizers include heat stabilizers and antioxidants. Examples of the stabilizer include phenol-based, amine-based, phosphorus-based, and thioether-based stabilizers. Among these, in this embodiment, it is preferable to include a phosphorus-based heat stabilizer.

[0029] Any known phosphorus-based heat stabilizer can be used. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds being particularly preferred.

[0030] Examples of the organic phosphite compound include distearyl pentaerythritol diphosphite, bis(decyl)pentaerythritol diphosphite, bis(tridecyl)pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite. Specific examples of such organic phosphite compounds include "ADK STAB (registered trademark; the same applies below) 1178," "ADK STAB 2112," and "ADK STAB HP-10" manufactured by ADEKA Corporation, "JP-351," "JP-360," and "JP-3CP" manufactured by Johoku Chemical Industry Co., Ltd., and "IRGAFOS (registered trademark; the same applies below) 168" manufactured by BASF.

[0031] As for the phosphorus-based heat stabilizer used in this embodiment, in addition to the above, the description in paragraphs 0127 to 0133 of JP 2022-067329 A can be referred to, the contents of which are incorporated herein by reference.

[0032] As the phenol-based antioxidant, a hindered phenol-based antioxidant is preferably used. Specific examples of hindered phenol-based antioxidants include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphate, 4,6-bis(octyl butylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.

[0033] Among them, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred. Specific examples of such hindered phenol-based antioxidants include "Irganox (registered trademark, the same applies below) 1010" and "Irganox 1076" manufactured by BASF, and "Adeka STAB AO-50" and "Adeka STAB AO-60" manufactured by ADEKA.

[0034] The content of the stabilizer in the resin composition of the present embodiment is usually 0.001 parts by mass or more, preferably 0.005 parts by mass or more, more preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). By setting the content of the stabilizer within the above range, the effect of adding the stabilizer is more effectively exhibited. The resin composition of the present embodiment may contain only one type of stabilizer, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0035] <<Release agent>> The resin composition of the present embodiment may contain a mold release agent. By blending the mold release agent, the mold releasability can be further improved. Examples of the release agent include aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane-based silicone oils, ketone waxes, and light amides. Of these, aliphatic carboxylic acids, salts of aliphatic carboxylic acids, and esters of aliphatic carboxylic acids and alcohols are preferred. For details about the release agent, please refer to paragraphs 0055 to 0061 of JP2018-095706A, the contents of which are incorporated herein by reference. When the resin composition of the present embodiment contains a release agent, the content thereof in the resin composition is preferably 0.01 to 3 mass %. The resin composition of the present embodiment may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0036] <Physical properties of resin composition> The resin composition of the present embodiment preferably has excellent impact resistance. Specifically, the resin composition of the present embodiment is retained in the cylinder of an injection molding machine for 7 minutes, and then injection molded at an injection speed of 30 mm / s to obtain a 3.0 mmt ISO multipurpose test piece. The notched Charpy impact strength measured at a temperature of 23°C based on ISO standard 179-1 is 13.0 kJ / m 2 The upper limit is not particularly set, but is preferably 25.0 kJ / m 2 Even if it is less than this, it will be sufficient to meet the required performance. The impact resistance is measured as described in the Examples section below.

[0037] The resin composition of the present embodiment preferably has excellent retention stability. Specifically, the melt volume rate (MVR) of the resin composition of this embodiment at 300° C. and a load of 1.2 kgf is 30 cm 3 / 10 minutes or less is preferable, 24cm 3 / 10 minutes or less is more preferable, 23 cm 3 / 10 minutes or less is more preferable, and 20 cm 3 It is preferable that the time is 10 minutes or more. The resin composition of the present embodiment has a melt volume rate (MVR) of 80 cm3 at 300°C and a load of 1.2 kgf after treating the pellets in a pressure cooker at 120°C for 100 hours. 3 / 10 minutes or less is preferable, 75cm 3 / 10 minutes or less is more preferable, and 30 cm 3 It is preferable that the time is 10 minutes or more. The resin composition of the present embodiment has a melt volume rate (MVR) of 60 cm before and after pellets are treated in a pressure cooker at 120°C for 100 hours at 300°C and a load of 1.2 kgf. 3 / 10 minutes is preferable, 55cm 3 / 10 minutes or less is preferable, and 50 cm 3 / 10 minutes or less is more preferable, and 10 cm 3 It is preferable that the time is 10 minutes or more. MVR is measured as described in the Examples section below.

[0038] The resin composition of the present embodiment may or may not have flame retardancy. The resin composition of the present embodiment may not have flame retardancy. For example, the resin composition may be molded into a test piece having a thickness of 2.0 mm and evaluated as NG (not satisfying V-0, V-1, or V-2) according to the UL-94 test.

[0039] <Method of producing resin composition> The method for producing the resin composition of the present embodiment is not limited, and a known method for producing a resin composition can be widely adopted. For example, the polycarbonate resin (A), titanium oxide particles (B), aromatic sulfonic acid metal salt (C), and other components to be mixed as necessary are mixed in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded with a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader. The temperature for melt-kneading is not particularly limited, but is usually in the range of 240 to 320°C.

[0040] <Molded products> The molded article of this embodiment is formed from the resin composition or pellets of this embodiment. The above-mentioned resin composition (for example, pellets) is molded into a molded article by various molding methods. The shape of the molded article is not particularly limited and can be appropriately selected depending on the use and purpose of the molded article, and examples thereof include film-like, rod-like, cylindrical, ring-like, circular, elliptical, polygonal, irregular, hollow, frame-like, box-like, panel-like, and button-like shapes.

[0041] The method for forming the molded article is not particularly limited, and a conventionally known molding method can be adopted, for example, injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding) molding, rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, pressure molding, etc. In particular, the resin composition of this embodiment is suitable for molded articles obtained by injection molding, injection compression molding, and extrusion molding. However, it goes without saying that the resin composition of this embodiment is not limited to molded articles obtained by these methods.

[0042] The molded article of this embodiment can be widely used for molded articles containing polycarbonate resin, particularly optical parts. Specifically, it is preferably used in electrical / electronic equipment / parts, OA equipment / parts, information terminal equipment / parts, machine parts, home appliances, vehicle parts, building materials, various containers, leisure goods / miscellaneous goods, lighting equipment, etc., and more specifically, it is preferably used for power covers, lighting lenses, lighting covers, light guiding members, etc. More specifically, it can be used for light guides and lenses that guide light from light sources such as LEDs in headlamps, rear lamps, fog lamps, etc. for vehicles such as automobiles and motorcycles. In particular, it can be preferably used for light guides for automobile lighting or light guides for lighting. For the use of the resin composition of this embodiment, in addition to the above, the descriptions in paragraphs 0098 to 0105 of JP 2020-189992 A can be referred to, the contents of which are incorporated herein by reference. EXAMPLES

[0043] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.

[0044] 1. Raw materials The raw materials shown in Tables 1 and 2 below were used. [Table 1]

[0045] In this example, potassium diphenylsulfone-3-sulfonate was used as the sulfonate metal salt (C). The manufacturer's name and product number are shown in Table 2. In addition, the amount of phosphate ions, sulfate ions, chloride ions, and the total amount of phosphate ions and sulfate ions in each potassium diphenylsulfone-3-sulfonate (KSS) were measured. The units are ppm by mass. The results are shown in Table 2. [Table 2] ND indicates not detected.

[0046] <Method for measuring the amount of phosphate ions, sulfate ions, and chloride ions> An appropriate amount of potassium diphenylsulfone-3-sulfonate (KSS) was dissolved in 20 mL of distilled water, and the presence or absence of phosphate ions, sulfate ions, and chloride ions was confirmed by ion chromatography from the detection peaks derived from each ion. The content was also calculated from the height and area of ​​each detection peak.

[0047] 2. Examples 1 to 6 and Comparative Examples 1 to 2 <Compound> The components (polycarbonate resin (A), titanium oxide particles (B), and sulfonic acid metal salt (C)) shown in Table 1 or Table 2 were blended in the ratios (amount relative to 100 parts by mass of polycarbonate resin, unit: parts by mass) shown in Table 3, and mixed uniformly in a tumbler mixer to obtain a mixture. A mixture was obtained using polycarbonate resin (A1) and polycarbonate resin (A2) with a melt volume rate (MVR, 300°C, 1.2 kgf) of 17.5 cm3 The mixture was adjusted to have a mixing rate of 10 minutes per minute. The mass ratio of polycarbonate resin (A1) to polycarbonate resin (A2) was about 77:13. This mixture was fed to a twin-screw extruder ("TEX25αIII" manufactured by Japan Steel Works, Ltd.), kneaded under conditions of a screw rotation of 700 rpm, a discharge rate of 20 kg / hour, and a barrel temperature of 260°C, and extruded in the form of strands from the tip of the extrusion nozzle. The extrudate was quenched in a water tank and cut and pelletized using a pelletizer to obtain pellets of the resin composition.

[0048] <Charpy impact strength (molding temperature 310℃, 7 minute dwell)> The pellets obtained above were dried at 120°C for 5 hours, and then weighed out in an injection molding machine (Shibaura Machine Co., Ltd., "EC75") at a cylinder temperature of 310°C, a mold temperature of 80°C, and a screw rotation speed of 80 rpm. The pellets were allowed to reside in the cylinder for 7 minutes, and then injection molded at an injection speed of 30 mm / s to produce ISO multipurpose test pieces (3.0 mmt). The ISO standard multipurpose test piece (ISO 3167 type A) obtained by the above-mentioned method was notched using a notching machine (Toyo Seiki Co., Ltd. "Notching Tool A-4 type") with a single tooth V-cutter (45°, R = 0.25 mm), a notch rotation speed of 300 rpm, and three notch cutting passes. At the same time, an 80 mm piece of the center was cut out using a slicer. The Charpy impact strength of the obtained notched Charpy test specimens was measured in accordance with ISO 179 (unit: kJ / m 2 ). The measurements were carried out at a measurement temperature of 23°C using a Charpy impact tester DG-CB manufactured by Toyo Seiki Co., Ltd.

[0049] <Normal MVR> The melt volume rate (MVR) of the resin composition (pellet) was measured by placing the sample pellet in the cylinder of a melt indexer after drying at 120°C for 5 hours, and heating it for 4 minutes at 300°C under a load of 1.2 kgf according to the ISO-1133 standard. The unit of MVR is cm 3 / 10min.

[0050] <MVR after PCT treatment> After treatment at 120 °C for 100 hours in a pressure cooker, the resin composition (pellets) was dried at 120 °C for 5 hours, placed in the cylinder of a melt indexer, and the MVR was measured in the same manner as the measurement of the normal MVR according to the ISO-1133 standard. The unit of MVR is cm 3 / 10 min as shown. Also, the difference between the MVR after PCT treatment and the normal MVR was calculated (unit: cm 3 / 10 min).

[0051]

Table 3

[0052] The resin composition of the present invention was excellent in impact resistance. Furthermore, the increase in MVR after PCT treatment could be effectively suppressed. That is, a resin composition excellent in heat and humidity resistance was obtained (Examples 1 to 6). On the other hand, when the content of sulfate ions was low (Comparative Examples 1 and 2), the impact resistance was clearly inferior. Furthermore, the thermal stability was also inferior.

Claims

1. For 100 parts by mass of polycarbonate resin (A), 5.0 to 20.0 parts by mass of titanium oxide particles (B); and 0.01 to 3.0 parts by mass of an aromatic sulfonic acid alkali metal salt and / or an aromatic sulfonic acid alkaline earth metal salt (C), The sulfate ion (SO ) in the aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) 4 2- The resin composition has a content of 5,000 to 50,000 ppm by mass.

2. Furthermore, the aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) contains 1,500 to 10,000 mass ppm of phosphate ions (PO 4 3- The resin composition according to claim 1 .

3. The resin composition according to claim 1 or 2, wherein the aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) comprises an alkali metal salt of diphenylsulfonic acid and / or an alkaline earth metal salt of diphenylsulfonic acid.

4. 3. The resin composition according to claim 1, wherein the aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) comprises potassium diphenylsulfone-3-sulfonate.

5. The resin composition according to claim 1 or 2, which is used for a light guide for an automobile lamp or a light guide for lighting.

6. Furthermore, the aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) contains 1,500 to 10,000 mass ppm of phosphate ions (PO 4 3- ), the aromatic sulfonic acid alkali metal salt and / or aromatic sulfonic acid alkaline earth metal salt (C) comprises potassium diphenylsulfone-3-sulfonate, The resin composition according to claim 1, which is used for a light guide for an automobile lamp or a light guide for lighting.

7. A pellet of the resin composition according to claim 1, 2 or 6.

8. A molded article formed from the resin composition according to claim 1, 2 or 6.

9. A molded article formed from the pellets of claim 7.

Citation Information

Patent Citations

  • Polycarbonate resin composition and molded article

    JP2019123809A

  • Transparent resin composition, resin molded body, lamp cover, lamp cover for vehicles, combination lamp cover, and vehicle

    WO2019172243A1